Determinants of Foreign Direct Investment Inflows in Central and Eastern European Countries - Stawicka, Magdalena (Oeconomia Copernicana, 2014)
In the paper the author tries to analyse the value of foreign direct investments inflow into certain Central and Eastern Europe countries and to assess determinants which cause these countries to attract large value of the foreign direct investments. Twenty countries of the aforementioned region were analysed. Ten of them belong to the European Union including three belonging to the Euro-zone. Additionally, the paper contains presentation of the most significant determinants of the foreign direct investments based on investors’ motives. In order to achieve the aforementioned goal, the author reviewed the literature on the subject paying special attention to the issues in question, and she presented the results of the survey focused on the FDI determinants in the economies which are the subject of this paper. The paper also contains results of two surveys conducted by the author in 2006 and 2012 regarding motives of the entrepreneurs who make foreign direct investments in the territory of the EU countries. Review of the theory, analysis of general empirical observations and own surveys of the author prove that the size of a market, the possibility to maximize profits and discounts and privileges for investors are the most substantial internal and external factors which encourage entrepreneurs to invest on foreign markets. Moreover, membership in the European Union and/or the Eurozone, as well as the warranty of macroeconomic stability of a country also pose a substantial advantage when an investor chooses the location for an investment.